PENGARUH ASOSIASI MEREK, PERSEPSI KUALITAS DAN GAYA HIDUP TERHADAP MINAT BELI SANDAL DAN SEPATU BATA CABANG KUNINGAN - Latipah, Riska (JBMI (Jurnal Bisnis, Manajemen, dan Informatika), 2017)
This study against the background by increasing the competition in the industry sandals and shoes in Indonesia. This affects the sales of sandals and shoes Bata. This study also aims to analyze and test the effect of brand association, perceived quality and lifestyle of purchase intention Bata sandals and shoes Kuningan branch. Then analysis of data obtained using quantitative and qualitative analysis. Quantitative analysis includes: validity and reliability, data normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple regression analysis, hypothesis testing through t test and F, as well as the coefficient of determination (R ²). Qualitative analysis is the interpretation of the data obtained in the study and the results of data processing that has been carried out by members of description and explanation. Hypothesis testing using t test showed that the variables of brand association and perceived quality is significantly positive effect on purchase intention. Figures adjusted R2 of 0.585 indicates that 58.5% variable purchase intention can be explained by the three independent variables in the regression equation. While the rest of 41.5% is explained by other variables outside three variables used in this study.